Community-based assessment of bone health and associated factors among elderly in an urban slum of Kolkata, West Bengal: a cross-sectional study - Kousik Nag; Jayita Pal; Sanjoy Kumar Sadhukhan; Rama Ranjan Pati; Rohit Dalmia; Arindam Chatterjee (International Journal Of Community Medicine And Public Health, 2026)
Background: Osteoporosis and osteopenia are common metabolic bone disorders among the elderly, increasing fracture risk and disability. Urban slum populations are particularly vulnerable due to poor living conditions, limited health care access, and low awareness. This study aimed to assess bone mineral density (BMD) and its determinants, and to examine awareness and health-seeking behaviour among elderly residents of the Chetla slum, Kolkata, West Bengal. Methods: A community-based cross-sectional study was conducted from January 2024 to February 2026 among 240 adults aged ≥60 years residing in the Chetla slum for at least one year. Participants were selected using a two-stage cluster sampling method. Data on sociodemographic characteristics, lifestyle, morbidity, and bone health awareness were collected via structured interviews. Anthropometry was measured using standard methods, and BMD was assessed at the calcaneus using a portable quantitative ultrasound densitometer. Osteopenia and osteoporosis were defined according to WHO criteria. Bivariate and multivariable logistic regression analyses identified independent predictors of low BMD. Results: Mean participant age was 63.6±3.6 years; 67.5% were male. Low BMD was observed in 77.5% of participants. Independent predictors of low BMD included age >63 years (AOR 4.27, 95% CI 1.59-11.50), lower educational attainment (AOR 9.68, 95% CI 3.42-27.35), low physical activity (AOR 4.65, 95% CI 1.29-16.81), and lower socioeconomic status (AOR 2.10, 95% CI 0.96-4.57). Awareness of BMD testing was only 20%, and 35.5% of those with low BMD had not sought treatment. Conclusions: Elderly residents of the Chetla slum exhibit a high prevalence of low BMD. Community-level interventions including routine BMD screening with portable densitometers, promotion of weight-bearing physical activity, nutritional supplementation, and improved access to geriatric care are recommended to reduce osteoporosis-related morbidity.